Multiple sclerosis patients' understanding and preferences for risks and benefits of disease-modifying drugs: A systematic review - Reen, G; Silber, E; Langdon, D (Elsevier, 2016)
Background: Multiple sclerosis (MS) patients are faced with complex risk-beneﬁt proﬁles of disease-modifying drugs (DMDs) when making treatment decisions. For effective shared decision-making, MS patients should understand the risks and beneﬁts of DMDs and make treatment decisions based on personal preferences. Methods: This is an inclusive systematic review to primarily assess current understanding of MS patients for information about DMDs provided during the standard healthcare system.The secondary aim assesses MS patients'preferences for speciﬁc risks and beneﬁts of treatments. A systematic search was conducted using PubMed,Embase and Google Scholar. A total of 22 studies were reviewed across both aims. Relevant quantitative and qualitative data was extracted by two authors. A narrative synthesis was conducted due to heterogeneity of research ﬁndings. Results: There was a trend for DMD risks to be generally underestimated and DMD beneﬁts to be generally overestimated by MS patients. Treatments that could potentially offer substantial symptom improvement, delay in disease progression, or reduction in relapses were preferred even at the expense of higher risks. Conclusions: Many patients' experience of information during the standard healthcare system does not provide satisfactory understanding of the risks and beneﬁts of DMDs. Effective ways to communicate risk and beneﬁt DMD information when making shared treatment decisions needs to be identiﬁed. Patient preferences of DMD risks and beneﬁts should also be taken into account